Optimasi Penjadwalan Mata Pelajaran Pada Kurikulum 2013 Dengan Algoritme Genetika (Studi Kasus: SMA Negeri 3 Surakarta) - Radita Noer Pratiwi; Imam Cholissodin; Putra Pandu Adikara (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Scheduling is one of the most difficult computing problems to solve. Problems in scheduling also occur in SMA Negeri 3 Surakarta which has implemented the 2013 curriculum with the system of university credit unit which for the implementation consists of two courses, namely 4 semester program and 6 semester program. Genetic algorithm is a search method that can be used to obtain optimal solution. Representation of chromosome in the research is divided into two segments, those ares chromosome length 748 for 6 semester program and 86 4 semester program. The optimal solution is obtained from the test that conducted 10 times and obtained the optimal parameter value of population size 600 individuals, the number of generations 1000 times, the value of cr 0.5 and the value mr 0.5. The results of the optimal solution in the form of course schedules for the 6 semester program and 4 semester program obtained from the highest fitness value of 0.16208. The result of the solution obtained from the highest fitness value is not optimal because there are still violations on the constraint in the scheduling of the courses in SMA Negeri 3 Surakarta.